2015
DOI: 10.1016/j.addbeh.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Playing Tetris decreases drug and other cravings in real world settings

Abstract: Most research on cognitive processes in craving has been carried out in the laboratory and focuses on food craving. This study extends laboratory findings to real world settings and cravings for drugs or activities as well as food. Previous laboratory research has found that playing Tetris reduces craving strength. The present study used an ecological momentary assessment protocol in which 31 undergraduate participants carried iPods for a week and were prompted 7 times each day, by SMS message, to use their iP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 37 publications
2
30
1
Order By: Relevance
“…Engaging in this visuospatial cognitive activity when memories are activated is proposed to help impede traumatic flashbacks in PTSD by interfering with memory consolidation (37). Preliminary findings have also shown promise for using Tetris to reduce cravings (44). …”
Section: Types Of Applied Gamesmentioning
confidence: 99%
“…Engaging in this visuospatial cognitive activity when memories are activated is proposed to help impede traumatic flashbacks in PTSD by interfering with memory consolidation (37). Preliminary findings have also shown promise for using Tetris to reduce cravings (44). …”
Section: Types Of Applied Gamesmentioning
confidence: 99%
“…It has been used in research to promote cognitive enhancement (e.g. Belchior et al, 2013; Okagaki & Frensch, 1994), treat amblyopia or ‘lazy eye’ (Li et al, 2013), dampen vividness, and emotionality of autobiographical memories (Engelhard, van Uijen, & van den Hout, 2010), reduce cravings (Skorka‐Brown, Andrade, & May, 2014; Skorka‐Brown, Andrade, Whalley, & May, 2015), prevent intrusive memories of psychological trauma (Holmes, James, Coode‐Bate, & Deeprose, 2009; Iyadurai et al, 2017; James et al, 2015; James, Lau‐Zhu, Tickle, Horsch & Holmes, 2016b), and lessen mania‐related mental images (Davies, Malik, Pictet, Blackwell, & Holmes, 2012). Little is currently known about the cognitive mechanisms underpinning the benefits of Tetris, but one hypothesis emerging from the clinical psychology literature is that it selectively taxes visuospatial working memory (WM; Holmes et al, 2009; James et al, 2015).…”
mentioning
confidence: 99%
“…A recent study found that playing Tetris decreased cravings for drugs, food, and activities, including gaming (SkorkaBrown, Andrade, Whalley, & May, 2015). Increasingly, K-12 schools are building in digital game-based learning.…”
Section: The Problem At Handmentioning
confidence: 99%